2015
DOI: 10.1177/1535370215584889
|View full text |Cite
|
Sign up to set email alerts
|

Wnt5a attenuates hypoxia-induced pulmonary arteriolar remodeling and right ventricular hypertrophy in mice

Abstract: Hypoxic pulmonary hypertension (HPH), which is characterized by pulmonary arteriolar remodeling and right ventricular hypertrophy, is still a life-threatening disease with the current treatment strategies. The underlying molecular mechanisms of HPH remain unclear. Our previously published study showed that Wnt5a, one of the ligands in the Wnt family, was critically involved in the inhibition of hypoxia-induced pulmonary arterial smooth muscle cell proliferation by downregulation of b-catenin/ cyclin D1 in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Wingless (Wnt) signaling pathway is divided into canonical signaling pathway and non-canonical signaling pathway. As a member of Wnt family, mounting evidence indicated that wnt5a involved in the pathogenesis of PH [13,14,23,24], wnt5a was reported to have the role of regulating human endothelial cell proliferation and migration via noncanonical signaling [25] and inhibiting hypoxia-induced PASMC proliferation via suppression of of β1-catenin/cyclin D1 [26].…”
Section: Discussionmentioning
confidence: 99%
“…Wingless (Wnt) signaling pathway is divided into canonical signaling pathway and non-canonical signaling pathway. As a member of Wnt family, mounting evidence indicated that wnt5a involved in the pathogenesis of PH [13,14,23,24], wnt5a was reported to have the role of regulating human endothelial cell proliferation and migration via noncanonical signaling [25] and inhibiting hypoxia-induced PASMC proliferation via suppression of of β1-catenin/cyclin D1 [26].…”
Section: Discussionmentioning
confidence: 99%
“…The measurements were performed as previously described [ 16 , 17 ]. Following anaesthesia of the mice with 2% sodium pentobarbital (50 mg/kg i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Pulmonary artery resistance vessels from patients with idiopathic PAH demonstrated endothelial upregulation of β-catenin in idiopathic PAH vessels that correlated with upregulation of RhoA, ROCK, and Rac1 as assessed by immunohistochemistry and qPCR ( Laumanns et al, 2009 ). Finally, downregulation of β-catenin reduces hypoxia-induced PASMC proliferation and PA remodeling in hypoxia models of PH ( Yu et al, 2013 ; Alapati et al, 2014 ; Jin et al, 2015 ). These data together indicate a potential role for β-catenin activation downstream of stiffness-induced vascular remodeling in PH.…”
Section: Key Molecular Pathways Involved In Mechanobiological Feedbacmentioning
confidence: 98%